Respuesta :

r3t40
Hi,

Work:

[tex] \frac{2}{3x} + 6 = \frac{1}{2} + \frac{1}{4x} [/tex]

1. Move expression 1/4x to the left side and change its sign, also move constant -6 to the right side and change its sign. Now you equation looks like this:

[tex] \frac{2}{3x} - \frac{1}{4x} = \frac{1}{2} - 6[/tex]

2. Write all numerators above the least common denominator 12x.

[tex] \frac{5}{12x} = \frac{1}{2} - 6[/tex]

3. Calculate the difference between 1/2 and 6.

[tex] \frac{5}{12x} = - \frac{11}{2} [/tex]

4. Simplify equation using cross multiplication.

[tex]10 = - 132x[/tex]

5. Switch the sides of equation.

[tex] - 132x = 10[/tex]

6. Divide both sides of equation by -132.

[tex]x = - \frac{5}{66} [/tex]

7. Results:

[tex]x = - \frac{5}{66} = - 0.075[/tex]

Hope this helps.
If you have any questions about the answer comment below. Thank you!

r3t40